Supporting elementary school children’s skill and concept understanding in solving combinatorics problems - Arwadi, Fajar; Bustang, B. (Universitas Pendidikan Ganesha, 2018)
The present research is the preliminary part of a large-scale design research aimed at supporting students to use effective strategies and to reach multiplication concept by designing instructional activities in the topic of multiplication principle covering two-dimensional as well as three-dimensional problems. They were conducted in two cycles of which 10 to 11-year-old elementary school children actively participated. Design research then was chosen to reach the set goal. Specifically, in each cycle, hypothetical learning trajectory was set by applying the principle of Realistic Mathematics Education. Reflecting on the activities of both cycles, the findings suggest that by creating hands-on activity, the students are able to make all different possible combinations of each kind of object. Besides that, stemming from pairing one object to the other kind of objects, the students are simplified to use efficient strategy for the next increasingly complex problems. The increasing number problem facilitates students to grasp the use of multiplication in solving the problems. However, the understanding of students in multiplication should be firmly established by the guide of the teacher since they just made inductive reasoning of the solution patterns of the problems